Ameer hamza koh qaaf main - Jahangir Maqbool (Feroz & Sons Lahore, 2008)
Ameer Hamza Ko Qaf Mein is an adventurous tale set in a mythical world, where Ameer Hamza embarks on a daring journey to the mystical mountains of Qaf, facing challenges and discovering hidden truths.